Pharmacotherapy for Alcohol Use Disorders: Physicians’ Perceptions and Practices - Ponce Martinez, Caridad; Vakkalanka, Priyanka; Ait-Daoud, Nassima (Frontiers in Psychiatry, 2016)
Background and Objectives Alcohol use disorders (AUDs) are an important cause of morbidity and mortality. Despite the NIAAA’s recommendations that medications be considered for patients with alcohol dependence, the mainstay of treatment has been counseling. We designed a survey to assess the treatment practices of Psychiatrists and Family Medicine (FM) physicians, in an effort to identify barriers to the use of pharmacotherapy and develop strategies to increase physician knowledge and utilization of these medications. Methods An anonymous online survey was sent to FM physicians and Psychiatrists nationwide. The survey collected demographic information and assessed prescription of medications in treating AUDs, including FDA-approved medications and other medications used off-label for this purpose. We also examined factors that would lead to an increase in AUDs pharmacotherapy. Results A total of 491 surveys were completed, with 475 responses included in the final analyses. 45.5% of participants were Psychiatrists vs. 54.5% FM physicians. 74.7% respondents had used medications to treat AUDs, with Psychiatrists more likely to have prescribed acamprosate, naltrexone, and several off-label medications. FM physicians were more likely to report efficacy concerns. A majority of all physicians sampled would increase pharmacotherapy of AUDs with increased training. Discussion In our sample, most physicians have used medications to treat AUDs. There were concerns about efficacy with all non-FDA approved medications, but limited treatment success even with FDA-approved medications. Greater education about pharmacotherapy, including predictors for treatment response amongst patients, should help alleviate some of the uncertainties reported with medications’ efficacy and lead to a more